Identification of Risk and Protective Factors For Burnout Among Correctional Officers: A Systematic Literature Review - Mu’almar Hartatriana Sahesti; Dian Veronika Sakti Kaloeti (Green Publisher, 2025)
The profession of correctional officers is classified as a high-stress occupation with significant task complexity. In addition to being responsible for the security of correctional facilities, officers are also tasked with the social rehabilitation of inmates under demanding, dynamic, and emotionally challenging working conditions. These multifaceted demands can lead to psychological fatigue and ultimately result in burnout, a chronic psychological condition characterized by emotional exhaustion, cynicism toward work, and reduced personal accomplishment. Burnout is shaped by the interaction of various risk and protective factors, stemming from both individual and organizational domains. This study employs a Systematic Literature Review (SLR) approach guided by the PRISMA framework. Articles were retrieved from major databases including Scopus, Science Direct, EBSCO, and SAGEpub using the following keywords: (